2009
DOI: 10.1111/j.1600-6143.2009.02596.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Th1 and Cytotoxic Phenotype in Biopsies from Renal Transplant Recipients with Transplant Glomerulopathy

Abstract: †SH and HM contributed equally to this work.Transplant glomerulopathy (TGP) appears to be a pathogenic feature of chronic antibody-mediated rejection, but the pathogenesis of this histologic entity is still poorly understood. Previous studies suggest the involvement of lymphocytes but the phenotypes of these cells have never been analyzed. Here, we report the first study of mRNAs for specific markers of CD4+ T cells including Th1 (T-bet and INFc ), Th2 (IL4 and GATA3), Treg (Foxp3) and Th17 (IL-17 and RORc t) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 20 publications
3
34
1
Order By: Relevance
“…8 This profile was associated with transcript coding for granzyme B (GZM-B) in the graft. [9][10][11] Similar observations made in the blood of CAMR patients reported a restricted TCR Vb repertoire, an increase in IFN-g, GZM-B, and perforin-1 (PERF-1) transcripts, and an increase in CD8 T cells. [12][13][14] These observations suggest that alteration in the TCR Vb repertoire of CD8 T cells may be associated with kidney dysfunction.…”
supporting
confidence: 61%
“…8 This profile was associated with transcript coding for granzyme B (GZM-B) in the graft. [9][10][11] Similar observations made in the blood of CAMR patients reported a restricted TCR Vb repertoire, an increase in IFN-g, GZM-B, and perforin-1 (PERF-1) transcripts, and an increase in CD8 T cells. [12][13][14] These observations suggest that alteration in the TCR Vb repertoire of CD8 T cells may be associated with kidney dysfunction.…”
supporting
confidence: 61%
“…We then can hypothesize that such peripheral expansions, and particularly in patients with chronic rejection, could be related to dominant indirect [3] or direct [30] alloimmune responses against the graft. The role of T cells and especially CD8 1 T cells had been likely undermined in the process of chronic rejection, whereas several studies confirmed the presence of CD8 1 T cells infiltrate in the graft [31][32][33]. Moreover, we have shown that blood of animals (as reported here in patients) with chronic rejection exhibited strong alteration of the CD8 1 T-cell repertoire [34].…”
Section: Discussionmentioning
confidence: 55%
“…Our results showed increased expression of QCAT but not of GRIT, DSAST, ENDAT, or NKAT, suggesting cytotoxic T cellmediated but not antibody-mediated chronic injury. Homs et al reported increased expression of IFN-g, T-bet (a marker for Th1 CD4 T cells), and granzyme B (a CD8 marker) in TGP biopsy specimens, suggesting an active T cell-mediated inflammatory and cytotoxic process in the pathogenesis of TGP (11). Several other studies have also recognized that an increased cellular immune response involving T cells and monocytes is associated with the development of TGP (12)(13)(14).…”
Section: Discussionmentioning
confidence: 94%
“…TGP is reported to be associated with donor-specific antibody (DSA), especially class II DSA (5,8), but histologic evidence of TGP may be seen without C4d and DSA (9). Increased chemokine (CXCL9 and CXCL10) and chemokine receptor (CXCR3) expression by glomerular leukocytes, which is associated with effector T cell activation (10) and other T cell-mediated inflammatory or cytotoxic processes (11)(12)(13)(14), have been demonstrated in TGP biopsy specimens. Nonimmune mechanisms may also be associated with TGP, as suggested by a recent report of hepatitis C virus infection (36%) and thrombotic microangiopathy (32%) in 25 patients with TGP (15).…”
Section: Introductionmentioning
confidence: 99%